Early Outcome of Laparoscopic Abdomino-perineal Resection (APR) in Low Rectal and Anal Cancer- Our Initial Experience in Bangabandhu Sheikh Mujib Medical University - Rahman, Md Rayhanur; Hossain, Md Shahadat; Taher, Md Abu; lslam, Md Rashidul; Lima, lsmat Jahan; Alam, Md Ariful; Salahuddin, Gazi Muhammad; Khan, Tariq Akhter; Naznin, Kazi Nasid (Journal of Surgical Sciences, 2019)
Background: Colorectal cancer is the second most common malignancy in the western countries and the rectum is the most frequent site involved. Carcinoma of the lower part of the rectum involving the anal canal and carcinoma of the anal canal are now successfully managed by laparoscopic abdomino-perineal resection (APR) and postoperative morbidities are less and recovery is uneventful. In the current age of minimally invasive surgery, laparoscopic surgery for colon cancer has been established as equivalent to conventional open surgery in terms of oncological clearance. The purpose of the study is to compare the early outcomes of laparoscopic abdomino-perineal resection (LAPR) surgery in low rectal and anal cancer patients in terms of surgical site infections, postoperative pain, recovery, hospital stay and margin clearance of tumor with that of open abdomino-perineal resection (OAPR) surgery. Methods: This randomized controlled trial was carried out in the Colorectal Surgery Unit of Bangabandhu Sheikh Mujib Medical University, Dhaka from May, 2012 to April, 2013. 50 patients in low rectal and anal canal cancers were randomized into two groups with 25 patients in conventional open abdomino-perineal resection (OAPR) and rest 25 patients in laparoscopic abdomino-perineal resection (LAPR). Early outcome variables after surgery were evaluated. Results: Demographic data and baseline characteristics are equivalent in both groups of population. Tumors were more common in rectum (80% and 76%), most of the tumors were adenocarcinomas (80% and 72%) and most of the tumors were present in stage-II (40% and 48%) with grade-2 (64% and 52%) in LAPR and OAPR groups respectively. During early post-operative follow up, abdominal surgical site infection was found more in conventional open abdomino-perineal resection (OAPR) patients than that of laparoscopic abdomino-perineal resection (LAPR) patients (p =0.001). Other morbidity and colostomy related complications were not significant in early post-operative period in both groups of population. Degree of pain was also less after laparoscopic abdomino-perineal resection (p=0.001 ). Stoma function occurred earlier after Laparoscopic abdomino-perineal resection (p =0.017) and ambulation, feeding liquid and feeding solid all had no difference for both groups. Shorter mean length of postoperative hospital stay and early hospital discharge was possible after Laparoscopic abdomino-perineal resection (p =0.001 ). Oncologic parameters were equivalent to those with open procedures. Conclusion: The patients undergoing laparoscopic APR for low rectal and anal canal carcinoma have overall superior outcomes in terms of surgical site infection, postoperative pain, postoperative hospital stay and has equivalent oncological clearance as with those with open procedures. Journal of Surgical Sciences (2014) Vol. 18 (2) : 57-61